Analisis Metakognitif Siswa dalam Pemecahan Masalah Dimensi Tiga - Sulistyawan, David, Masduki, S.Si., M.Si (2016)
This study aimed to describe the profile of metacognitive students with high math ability, medium, and low in problem solving three-dimensional views of aspects of metacognitive skills of planning, monitoring, evaluation. This research is a qualitative research. The timing of the studies in the second semester of the 2015/2016 academic year. Subjects in this study were class XI SMK Muhammadiyah 5 Karanganyar totaling 23 students. The data collection technique using the test method, interviews, observation, and documentation. Data validation was done by triangulation method by comparing the test data, interviews, observation and documentation. Data analysis technique conducted in stages, data reduction, data presentation, verification and conclusion. The results were obtained high math ability students can use metacognitive skills aspects of planning, monitoring, and evaluation to the maximum. Mathematical ability students were able to use metacognitive skills planning aspect to the maximum, but have not been able to use metacognitive skills aspects of monitoring and evaluation to the maximum. While the low-ability students mathematics can not use metacognitive skills aspects of planning, monitoring, and evaluation to the maximum.